(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Atherosclerosis of the carotid artery is a major risk factor for stroke and cardiovascular diseases. Parathormone (PTH), primarily known for its role in calcium and phosphate metabolism, has been increasingly implicated in vascular pathophysiology. This review explores the potential mechanisms by which PTH contributes to carotid atherosclerosis, including endothelial dysfunction, vascular calcification, oxidative stress, and inflammation. Understanding these pathways could provide new insights into the prevention and management of atherosclerotic diseases. This review examines the role of PTH in the pathogenesis of carotid atherosclerosis and its potential implications for cardiovascular risk management. PTH has pleiotropic effects on the cardiovascular system. Beyond its classical role in bone metabolism, it exerts direct effects on vascular smooth muscle cells (VSMCs), endothelial cells, and inflammatory pathways.